Passing Power Sensors and Multiprobe Microwave Multimeter on Its Base - Volkov, V. M.; Nikitenko, O. M.; Zaichenko, O. B.; Zharko, Yu. G.; Isichko, A. L. (SPIE, 2006)
The mathematical modeling of thin wall waveguide heating process allows to determine the law of temperature field distribution on their surface. The new physical models of sensors on the absorbing wall principle in the coaxial transmission line were proposed and dissipative losses dependence on frequency in one, two and three layer absorbing wall was analyzed. Methods of calculation and designing of the both quasipoint and extended sensors, located on the narrow and wide waveguide walls were proposed: minimization of effective reflection.
Keywords: microwave measurement; reflection coefficient; microwave sensor; passing power; waveguide; temperature field; dissipative losses